FORMING A COMPETENT PRACTICAL THEOLOGY: A STUDY OF THE SUB-FIELD OF PRACTICAL THEOLOGY IN THE FACULTY OF THEOLOGY - Maria Elisa Tulangow (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the formation and development of practical theology as a sub-field within the Faculty of Theology at Universitas Kristen Indonesia Tomohon (UKIT), under the auspices of the Yayasan Gereja Masehi Injili di Minahasa (GMIM) Dominee Albertus Zakarias Runturambi Wenas. Employing a qualitative and interpretive approach, informed by Osmer's four tasks of practical theological interpretation, the research examines how practical theology is conceptualized, structured, taught, and experienced within the institution. Data were collected through interviews with faculty members and students, document analysis, participant observation, and focus group discussions. Findings reveal that while there is growing awareness of practical theology's importance, its implementation remains inconsistent across the curriculum. Practical theology is often viewed more as a set of ministerial skills than as a reflective academic discipline. Structural limitations include minimal credit hour allocation and poor integration with foundational theological fields. Pedagogical approaches remain largely lecture-based, with limited use of experiential learning strategies. Field education experiences are valuable, but lack consistent theological supervision and reflection. Despite these challenges, UKIT demonstrates a strong commitment to contextual theological education, though deeper incorporation of indigenous theological resources is needed. The study concludes that meaningful reform requires a multi-dimensional approach involving conceptual reorientation, curricular revision, pedagogical innovation, strengthened field education supervision, and deepened contextual engagement. By adopting an integrative and reflective model of practical theology, UKIT can better equip theological leaders who are not only knowledgeable but also spiritually attuned and contextually responsive.